MENDORONG KOLABORASI ANTARA SEKTOR SWASTA, PEMERINTAH, DAN MASYARAKAT MELALUI CROWDFUNDING UNTUK MENINGKATKAN KUALITAS PENDIDIKAN - Arini, Fauzia (Educatus, 2024)
This research investigates crowdfunding collaboration between the private sector, the Sukabumi City Government, and civil society organizations in supporting education in Sukabumi City, West Java. Through a qualitative approach with a case study, data were obtained from in-depth interviews and document analysis. The results indicate that the collaboration successfully generated several crowdfunding initiatives with positive impacts, such as procuring school supplies, building educational facilities, and providing scholarships. Active collaboration among the involved parties is key to the success of these projects. However, challenges such as complex coordination and the need for competent human resources are still faced. The implications of this research highlight the importance of collaboration in improving the quality of education, with an emphasis on adapting strategies in the local context. These findings make a significant contribution to understanding the effectiveness and sustainability of crowdfunding collaborations in supporting education at the local level.